Spatial Mismatch Between Black Mangrove Avicennia germinans and Associated Herbivores Along the Range Edge Ecotone - Jamie E. Thompson; Steven C. Pennings; Anna R. Armitage (Estuaries and Coasts, 2026)
Globally, many plant communities are reorganizing in response to climate change, often at different rates than associated fauna. Asynchrony in range expansion between plants and fauna could alter biotic constraints on plant populations. Tropical mangroves are limited by folivory, but little is known about the importance of herbivory on mangroves near distributional range limits in subtropical regions. We hypothesized that herbivore abundance and herbivory intensity would vary along the extended range edge ecotone of Avicennia germinans (black mangrove) in the northern Gulf of Mexico, with higher pressure at southern sites where A. germinans stands were more extensive, and that leaf defensive characteristics would be enhanced in areas with more herbivory. We surveyed leaf damage, loss of yield, leaf defensive characteristics, and terrestrial arthropod abundance at four sites with varying levels of mangrove cover along the Texas (USA) coast. At southern sites with relatively high A. germinans cover, leaves had more than twice as much accumulated damage and up to 50% more loss of yield than at a northern site with low mangrove cover. The types of damage were more variable at southern than northern sites, suggesting higher consumer diversity. Herbivorous specialists on mangroves (e.g., mangrove buckeye Junonia spp.) were only detected at the southern sites with high mangrove cover. Leaf traits associated with decreased plant palatability (e.g., sclerophylly, phenolics) were variable among sites. Patterns at the four sites suggested asynchrony in mangrove and herbivore range expansion, where A. germinans distribution extended beyond the range of its associated consumers. Sampling a larger number of sites in future work could confirm this asynchrony and determine the importance of this spatial mismatch for the success of mangrove expansion.